Evaluation of the Effectiveness of the Daihatsu Program Based on the Kirkpatrick Model in Partner Vocational Schools - Widiyanti; Prihandono, Billy Yusuf; Nurhadi, Didik (EDUTEC : Journal of Education And Technology, 2025)
This study evaluates the effectiveness of the Daihatsu Program in the Light Vehicle Engineering subject at partner vocational schools, namely SMK Islam 1 Blitar and SMK PGRI 3 Malang, using Kirkpatrick's four-level evaluation model. Employing a descriptive qualitative approach through interviews, observation, and documentation, the data were analyzed inductively. The findings reveal positive outcomes at each evaluation level. At the reaction level, both teachers and students responded with great enthusiasm to the industry-based learning. At the learning level, there was a marked improvement in students' conceptual understanding and technical competencies. At the behavior level, students demonstrated significant development in their work attitudes and discipline. Most importantly, at the results level, the program not only enhanced the quality of graduates, making them more job-ready, but also strengthened the strategic partnership between the educational institutions and the industry. Therefore, the Daihatsu Program proves to be an effective and tangible implementation of the link-and-match concept, successfully bridging the gap between the school curriculum and real-world industry demands. It stands as a successful model for developing relevant and sustainable vocational education in Indonesia.